Future Teachers Conceptualizing Democracy in Pre-war Ukraine, in Palestine, and Norway: Five Dimensions and the “wikied” Democracy Conceptions - Christensen, Ingrid; Kolesnyk, Larysa Dahl; Adwan, Sami; Matusevych, Tetiana (Nordic Journal of Comparative and International Education (NJCIE), 2024)
This article presents a qualitative study of future teachers’ conceptions of democracy in Ukraine, Palestine, and Norway during a pre-war and pre-pandemic period. In recent years, there has been a noticeable decline in the understanding of the democratic concept and reduced engagement, particularly among youth, coinciding with an assumed global recession of democratic recession. However, democracy also evolves with societal developments, whereas education holds the mandate to renew democratic values in society. This study therefore aims to explore student teachers’ own definitions of the democracy concept. Employing a grounded theory approach, we compare the written responses of 619 student teachers from Ukraine, Palestine, and Norway. The analysis reveals that despite different emphases, democracy is articulated along five dimensions: 1) political systems, 2) political culture, 3) values, 4) actions, and 5) actors. However, the study also indicates a striking finding: To our surprise, there were many identical responses across the data material, interpreted as wikied copy-paste responses, which indicate a distance and irony towards standardized democracy concepts. Consequently, democracy education is in a limbo between standardization and fostering new dimensions, whereas the teachers’ tasks will be challenging in providing democracy concepts born anew for the next generation.